Дерев’яні вироби з давньоруського Чернігова (матеріали розкопок 2006 р. на території Чернігівського дитинця) - Сергєєва, М.С.; Черненко, О.Є. (Археологія, 2016)
У статті проаналізовано дерев’яні вироби, виявлені в одній із будівель ХІІІ ст. на території Чернігівського дитинця в 2006 р. Окрім звичайного візуального обстеження, дерев’яні артефакти було вивчено з метою визначення сировини виробництва кожного виду виробів. Виявлено, що серед знахідок репрезентована продукція домашнього й професійного ремесла. Усі вироби виготовлені з місцевих порід дерева. The article deals with the analysis of woodwork found in one of the structures on the territory of Chernihiv dytynets in 2006. The stratigraphic data allow the authors to interpret the structure as a recessed part (basement) of a large building. It can be dated within the 13th century. Wooden objects found in the filling of the building included a chiseled dish, fragments of other chiseled and carved vessels, two hollowed containers, the bottom of the cooperage vessel, fragmented products made of bark, a spoon, and the remains of a loom. Some details of construction of the building were also found. Besides the usual visual examination, wooden artifacts were studied to determine the feedstock for every kind of product. Diagnosis of timber was conducted based on the specifics of its microstructure. The investigated set of wooden utensils from Chernihiv is traditional for Ancient Rus material culture. Among the findings are the products of home crafts (remains of loom and hollowed containers) and professional artisans (chiseled, carved and cooperage products) are both presented. They were made of local wood species, such as: pine (Pinus sylvestris), oak (Quercus sp.), maple (Acer sp.), lime (Tilia sp.), poplar/aspen (Populus sp.), and willow (Salicaceae). When using different species of wood, their properties and their conformity to products with different functions were taken into account. Статья посвящена анализу деревянных изделий, обнаруженных в одной из построек на территории Черниговского детинца в 2006 г. Данные стратиграфии позволяют интерпретировать сооружение как углубленную часть (подклеть) большой постройки. Ее можно датировать в рамках ХІІІ вв. Обнаруженные в заполнении постройки деревянные предметы включали точеное блюдо, фрагменты других точеных и резных сосудов, две долбленые емкости, дно бондарного сосуда фрагментированные изделия из коры, ложку, остатки ткацкого станка. Также были обнаружены детали конструкции постройки. Кроме обычного визуального исследования деревянные артефакты были изучены на предмет определения сырья для каждого вида изделия. Диагностика древесины проводилась по особенностям ее микроструктуры. Исследованный набор деревянной утвари из Чернигова является традиционным для древнерусской материальной культуры. Среди находок представлена продукция домашнего ремесла (остатки ткацкого станка, долбленые тарные емкости) и профессиональных ремесленников (точеные, резные и бондарные изделия). Они были изготовлены из местных пород дерева: сосны (Pinus sylvestris), дуба (Quercus sp.), клена (Acer sp.), липы (Tilia sp.), тополя/осины (Populus sp.), ивовых (Salicaceae). При использовании разных пород дерева учитывались его свойства и их соответствие изделиям с разными функциями.